Carrier mobility in field effect transistors based on copper-phthalocyanine thin films with different phase structure - Lkhamsuren, Enkhtur; Ragchaa, Galbadrakh (Scientific transaction of the National University of Mongolia. Physics, 2022)
Using annealing procedure at different temperatures after deposition at room temperature we obtained copper- phthalocyanine (CuPc) thin films with a — and p —phase structure. A phase structure of thin films was controlled by X-ray diffraction method, morphology was controlled by SEM. The field effect transistors was fabricated by high vacuum deposition of CuPc thin film (thickhess of 100 nm) on Si02 substrate which acting as gate contact. Gold drain and source contacts deposited on the top of active layer of FET. From measured current voltage measurements calculated mobility and concentration of charge carriers in FET. These parameters depend on phase structure of CuPc thin film, and characteristics of our FET are comparable with values of other authors. CuPc is commercially available macro cyclic metal complex that can be easily obtained in large quantity and high purity. Together with other phthalocyanine derivatives, the chemically and thermally stable CuPc has wide applications in dye processing, spectral sensitization, chemical sensors, and optical data storage [3-4]. The semiconducting behavior of metal phthalocyanines was first observed in 1948 and they have since attracted great interest in advancement of protptype organic semiconductors. Among the metal substituted phthalocyanines CuPc has been found superior properties [5-7], such as phenomena of field dependent and wavelength-dependent efficiency in an organic static induction transistors, and stabilizing role of CuPc layer on a highly stable organic electroluminescent device based on thin film Alq, and indicated a very weak interaction between CuPc and Au at the interface. In general, phthalocyanine materials can exist in several crystalline polymorphs, including a-, p -, x-and y - structure, and the most well known are the thermally metastable a- and p - [8-10], Phthalocyanine films deposited at room temperature usually consist of a-phase crystallites (at sublimation pressure of less than 10 Pa). At higher deposition pressures or at substrate temperature above 210°C, the p -phase directly obtained [11], Although it is well known that a-phase crystallites undergo a phase transformation into P -phase by treatment in various organic suspension media [12,13] or during annealing at higher temperatures [14,15], only some authors describe the nature of the a—>p phase transformation of copper phthalocyanine thin films with a thickness of less than 100 nm [8,14-15].